Design and Implementation of Multimedia Product on CV. Jocaidy Pelita Cemerlang - Desmond Lim; Erilia Kesumahati (ConCEPt - Conference on Community Engagement Project, 2023)
Information about a company is an important point of any business. Interest and decisions in business cooperation begin with knowing information about the company to work with. One of these information can be known through a company profile. UIB collaborate with CV. Jocaidy Pelita Cemerlang (JPC) in compiling a company profile company that serves scale problems in Batam City. The cooperation begins with an agreement in the form of a MoA and MoU between the UIB and CV. Jocaidy Pelita Cemerlang. The preparation of the company profile is carried out by collecting information and observing the company, then continued with the preparation with the help of the Canva application. The result of this collaboration is in the form of a company profile that provides information about JPC. It is hoped that this project can be useful for JPC and become an inspiration for other companies to develop their business.